Data aquisition and communication system for a brain-computer interface / Einly Lim - Einly, Lim (2005)
A Brain-Computer Interface (BCI) system that is being developed at the University of Malaya for the control of a prosthetic hand consists of a computer, a BCI box and a prosthetic hand. Electroencephalogram (EEG) signals are acquired using two or four electrodes placed on the scalp of a subject. In the BCI box, the EEG signals are amplified and filtered. The filtered signals are digitized and sent to a computer. Signal processing, feature extraction and classification are carried out in the computer. The classification results are sent to the controller to operate the prosthetic hand. The present thesis describes my contribution to the development of the digitizer and the communication system between the digitizer and the computer and other devices. The filtered EEG signals are digitized at a sampling rate of 256 Hz and with a resolution of 16 bits. The digitized data are sent to a computer through a universal serial bus (USB) wire or a Bluetooth unit. A main control program in the computer continuously reads the digitized data and transfers the data to a sub-program for signal processing, feature extraction and classification. The output decision of the classifier is sent to the controller to operate the prosthetic hand or to switch on one of four light emitting diode (LED) lights that represent devices.